Patient Satisfaction: A Tool towards Quality Improvement: http://doi.org/10.36351/pjo.v37i2.1150 - Sughra, Ume; Siddiqui, Manaal; Noorani, Sorath; Mansoor, Hassan; Kausar, Sultana (Pakistan Journal of Ophthalmology, 2021)
Purpose: To determine the importance of patient satisfaction as a tool for quality improvement. Study Design: Cross sectional survey. Place and Duration of Study: Pediatric Ophthalmology Department of Al-Shifa Trust Eye Hospital, Rawalpindi, from May 2017 to September 2017. Methods: This study included 500 individuals, who were caregivers of children visiting the hospital at the time of data collection. Individuals who visited departments other than pediatric department were excluded. Two groups were made. Group 1 included 300 individuals who were interviewed for to assess the patient satisfaction. On the basis of response, play area was made spacious, additional registration counters were placed and more reception staff members were hired to shorten the waiting and registration time, additional fans were installed in the waiting area and patient information was displayed on TV screens to aid uneducated patients and their attendants. Second group with 200 individuals were interviewed after these improvements. Pretested structured questionnaire was used to collect data regarding socio-demographic characteristics and experience of visit to the hospital. SPSS version 20 was used for descriptive and inferential data analysis. Results: Participants in this survey showed high level of satisfaction after interventions 45 to 65%.There was statistically significant association between satisfaction level and improvement in services was found (p < 0.001). Conclusion: Satisfaction level of patients depends upon the quality of services and medical care provided and it can be used as a good tool for improving the services in the hospitals. Key Words: Satisfaction, Outpatient department, Hospital.